1988
DOI: 10.1161/01.hyp.12.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the baroreceptor-heart rate reflex by 24-hour intra-arterial blood pressure monitoring in humans.

Abstract: SUMMARYThe baroreceptor control of the sinus node was evaluated in 10 normotensive and 10 age-matched essential hypertensive subjects in whom ambulatory blood pressure was recorded intraarterially for 24 hours and scanned by a computer to identify the sequences of three or more consecutive beats hi which systolic blood pressure (SBP) and pulse interval (PI) progressively rose (+ PI/ + SBP) or fell ( -PI/ -SBP) in a linear fashion, according to a method validated in cats. In normotensive subjects, several hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
365
5
13

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(408 citation statements)
references
References 25 publications
25
365
5
13
Order By: Relevance
“…17 Previous studies using sequence analysis have found that BRS values derived from baroreflex loading were comparable to those derived from unloading. 12 Importantly, in our study the proportion of positive and negative sequences did not change after treatment and thus the differences between positive and negative sequences do not account for the finding that BRS was increased after dihydropyridine therapy.…”
Section: Figurecontrasting
confidence: 63%
See 1 more Smart Citation
“…17 Previous studies using sequence analysis have found that BRS values derived from baroreflex loading were comparable to those derived from unloading. 12 Importantly, in our study the proportion of positive and negative sequences did not change after treatment and thus the differences between positive and negative sequences do not account for the finding that BRS was increased after dihydropyridine therapy.…”
Section: Figurecontrasting
confidence: 63%
“…Spontaneous BRS was assessed by analysis of the 24-h IABP recordings by an adaptation of the method originally described by Parati et al, 12 as we have previously reported. 13 Each IABP recording was sampled at 125 Hz, digitised into 12 bits and analysed by an Apple Macintosh micro-computer running Lab View software.…”
Section: Determination Of Baroreflex Sensitivitymentioning
confidence: 99%
“…There is evidence that a decreased BRS may carry an adverse prognosis in cardiac patients [Osterziel et al, 1995;Mortara et al, 1997;La Rovere et al, 1998]. For several years, the BRS was determined pharmacologically (phenylephrine, nitro-prusside) [McCall & Humphrey, 1983;Vanoli & Adamson, 1994] or mechanically Mancia et al, 1984;Takahashi et al, 1999] until in the 1980s innovative methods for BRS estimation were developed which are based on spontaneous heart rate and blood pressure fluctuations [Di Rienzo et al, 1985;Parati et al, 1988]. These methods evaluate arterial baroreflex function in the absence of external stimulations on the cardiovascular system, therefore defined as spontaneous.…”
Section: Baroreceptor Sensitivitymentioning
confidence: 99%
“…Di Rienzo and Parati introduced in the 1980s the sequence method [Di Rienzo et al, 1985;Parati et al, 1988] which was the first not requiring drug-injections. This time-domain method scans the beat-to-beat systolic pressure series to identify sequences with monotonic BP increases (or decreases) and synchronous BBI increases (or decreases).…”
Section: Baroreceptor Sensitivitymentioning
confidence: 99%
“…An example of this is represented by the assessment of HRV along with analysis of BPV from beatto-beat BP recordings, which complements the information provided by HRV analysis (by providing indices of vascular autonomic modulation). In addition, by applying modeling approaches which focus on the relationship between fluctuations of HR and BP (either in time or in the frequency domain), 26,27 it is also possible to assess other mechanisms of major importance for autonomic CV control such as the degree of spontaneous cardiac baroreflex sensitivity. Such an approach may provide a more comprehensive analysis of cardiovascular regulation mechanisms than that represented by the separate analysis of BP and HR variability alone.…”
mentioning
confidence: 99%